2010
DOI: 10.1677/joe-10-0057
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone modulation of proinflammatory cytokine and C-reactive protein expression in macrophages from older men and postmenopausal women

Abstract: Inflammation plays a central role in the development and progression of coronary heart disease (CHD). The sex hormones estrogen and testosterone have been shown to modify the inflammatory response by influencing cytokine expression in human macrophages obtained from younger individuals. The effect of these hormones on the expression of proinflammatory markers in macrophages obtained from a CHD age-relevant population has not been studied. Human monocyte-derived macrophages (HMDMs) were obtained from healthy no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 46 publications
6
90
0
5
Order By: Relevance
“…In fact, numerous previous studies have constantly reported that TC is significantly positively associated with IS in vivo [24,38,40,46,54], and both of them can be improved with MMIs, muscle mass indexes, were expressed as mean ± SD exercise [3,5,11,20,36,37,42,48]. The increased plasma TC in male rats during exercise is at least partially a result of lactate's effect on the secretion of testosterone [30,31], and testosterone may suppress the expression of proinflammatory cytokines such as tumor necrosis factor-alpha and interleukin-1 [8,32]. In experimental models, these proinflammatory cytokines disrupt normal insulin action in fat and muscle cells, and this may be the major factor in causing the whole body IR observed in patients with visceral adiposity [47].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, numerous previous studies have constantly reported that TC is significantly positively associated with IS in vivo [24,38,40,46,54], and both of them can be improved with MMIs, muscle mass indexes, were expressed as mean ± SD exercise [3,5,11,20,36,37,42,48]. The increased plasma TC in male rats during exercise is at least partially a result of lactate's effect on the secretion of testosterone [30,31], and testosterone may suppress the expression of proinflammatory cytokines such as tumor necrosis factor-alpha and interleukin-1 [8,32]. In experimental models, these proinflammatory cytokines disrupt normal insulin action in fat and muscle cells, and this may be the major factor in causing the whole body IR observed in patients with visceral adiposity [47].…”
Section: Discussionmentioning
confidence: 99%
“…5). The physiological and supraphysiological concentrations of testosterone reduced the expression and secretion of TNFa and IL1b in monocyte-derived macrophages obtained from a CHD age-relevant population, although no effects were observed on IL6 and CRP expression (Corcoran et al 2010). In another study, IL6 production was shown to be reduced in isolated human monocytes from a small healthy male population following in vitro testosterone treatment (Kanda et al 1996).…”
Section: Testosterone and Vascular Inflammationmentioning
confidence: 99%
“…Another reason may be that native sd-LDL has distinct properties to induce lipid accumulation in macrophages. It has recently been reported that estrogen-induced C reactive protein gene expression in human monocytederived macrophages was correlated with sd-LDL cholesterol levels, but not LDL cholesterol levels in the plasma used for incubation 19) . To investigate whether scavenger receptors might relate to the increase of lipid accumulation, we measured the expression (both mRNA and protein) of SR-A, CD36 and LOX-1 by macrophages.…”
Section: Discussionmentioning
confidence: 99%